(untitled) (International Journal of Religion, 2024)
Catholic is a global religion, so Catholic funerals organization expresses Catholic belief in the Resurrection and the cultural nuances of each nation. Over the past 70 years (from 1954 to 2024), the organization of Catholic funerals in Saigon (SG) - Ho Chi Minh city (HCMC) has undergone many changes because of urbanization influence and immigration waves as well as cultural diversity of local Catholic communities. This article will present some characteristics of Catholic funerals in SG-HCMC and important changes in dealing with the deceased's body.